The Six Characteristics of Andragogy and Future Research Directions in EFL: A Literature Review - Purwati, Diana; Mardhiah, Ainol; Nurhasanah, Enung; Ramli, Ramli (Elsya : Journal of English Language Studies, 2022)
The way in which adults learn is distinctive to how children learn, hence Andragogy differs from Pedagogy and so do the implications. Although several studies have attempted to discuss the andragogy and its principles, only few studies investigate its implementation and the practical guidance on how to employ each characteristic in the teaching and learning process. To fill this void, this paper reviews the concept of andragogy and highlights its six characteristics: self-concept, experiences, readiness to learn, motivation, need to know, and problem-centred learning. Employing a narrative review of 18 journal articles from reputable international journals, the study’s findings suggest that the six characteristics/principles of andragogy are applicable in designing teaching and learning materials, teaching activities, and assignments enacted by teachers. Future research is encouraged to delve into the practice of the six characteristics of andragogy in the teaching of English as a foreign language. The differences between adults and children learning and directions for further research in teaching English as a Foreign Language (EFL) is also discussed at the end of study.